2019
DOI: 10.1161/circinterventions.118.007546
|View full text |Cite
|
Sign up to set email alerts
|

Predictors, Incidence, and Outcomes of Patients Undergoing Transfemoral Transcatheter Aortic Valve Implantation Complicated by Stroke

Abstract: Background: Stroke remains one of the most devastating complications of transcatheter aortic valve implantation (TAVI). The aim of this study was to identify the incidence, timing, temporal trends, and predictors of stroke after TAVI and evaluate the outcomes of patients with stroke. Methods and Results: The CENTER-Collaboration is an international collaboration consisting of 3 national registries and 7 local registries or prospective cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 25 publications
6
82
1
Order By: Relevance
“…Transcatheter aortic valve implantation (TAVI) has been established as an effective treatment of severe aortic valve (AV) stenosis, reducing both clinical symptoms and mortality. Nevertheless, one of the most feared complications, namely the occurrence of stroke, is still observed in 2.4% of the patients undergoing TAVI [1]. This complication is observed despite the expansion to low-risk populations, the increase in operator experience and the development of improved valve-systems [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcatheter aortic valve implantation (TAVI) has been established as an effective treatment of severe aortic valve (AV) stenosis, reducing both clinical symptoms and mortality. Nevertheless, one of the most feared complications, namely the occurrence of stroke, is still observed in 2.4% of the patients undergoing TAVI [1]. This complication is observed despite the expansion to low-risk populations, the increase in operator experience and the development of improved valve-systems [2].…”
Section: Introductionmentioning
confidence: 99%
“…The cerebral emboli during TAVI are attributed to the dislodgement of aortic arch calcifications during the advancement of the catheter through the orifice and the expansion of the implanted valve crushing the calcified native valve [3]. Our previous research showed that stroke after TAVI is associated with poor outcomes, including a sixfold increase of procedural mortality [1]. Nevertheless, clinically overt strokes are only the tip of the iceberg, since shortly after TAVI acute silent cerebral infarctions are visible with diffusion-weighted magnetic resonance imaging (DW-MRI) in up to 78% of the patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…For a detailed review on SBIs after TAVI, we recommend reading the article of Pagnesi et al [40] Risk Factors for Occurrence of CVEs Several risk factors for CVEs were identified, but they differ among studies, in particular depending on patient characteristics, including parameters, definition of events, and time points of assessment. Previous cerebrovascular disease and older age are two independent risk factors associated with early and late CVEs after TAVI and within the general population [41][42][43][44][45]. In an analysis of 10,982 patients from the CENTER collaboration, a GFR < 30 ml/min/1.73 cm 2 was an independent predictor of stroke at 30 days after TAVI [44].…”
Section: Clinical Impact Of Cvesmentioning
confidence: 99%
“…Previous cerebrovascular disease and older age are two independent risk factors associated with early and late CVEs after TAVI and within the general population [ 41 45 ]. In an analysis of 10,982 patients from the CENTER collaboration, a GFR < 30 ml/min/1.73 cm 2 was an independent predictor of stroke at 30 days after TAVI [ 44 ]. In another analysis, post-dilatation and valve dislodgement/embolization were independent predictors of an acute (≤ 24 h) CVE [ 43 ].…”
Section: Cerebrovascular Events In Cardiovascular Proceduresmentioning
confidence: 99%
“…Data from the international CENTER collaboration study (10,982 patients undergoing transfemoral TAVI) indicate a 30-day risk of stroke of 2.4% after TAVI, which was responsible for a 6-fold increase of 30-day mortality. 8 Independent predictors of stroke were previous cerebrovascular events and renal insufficiency. Strikingly, this study showed that stroke rate did not decline from the early years of TAVI procedures to more recent years.…”
mentioning
confidence: 99%